Pohon Literasi Sebagai Media Pembelajaran Dalam Peningkatan Kemampuan Literasi Siswa SMP di SMP Swasta Kartika 1-I Medan - Bina Melvia Girsang; Aulia Rahmadan; Arjun Pascal P; Nurul A Nasution; Putri Adinda Lestari (Yayasan Kajian Riset Dan Pengembangan Radisi, 2022)
The entry of covid-19 into Indonesia is having a lot of impact on students in Indonesia, covid-19 transforms offline learning methods to online. A decree from the minister of education to set up online learning causes students to adapt again to a new learning system. Teachers must prepare creative learning methods to attract students. So College Students Taught 4th in Kartika I-1 Junior High School Medan to create literacy trees as a sophisticated attractive learning for students.